Sustainability of Irrigation Practices and Water-Pricing Tools in Water-Stressed Tropical Countries: A Way Forward for Sustainable Water Governance - Tryphena Magdalene Jason; Carolin Arul; Melba Respina Bakthasingh; Vaishnudurga Parthipan (AgroEnvironmental Sustainability)
Increasing water stress threatens agriculture, livelihood, and sustainability in Tropical countries. Asian and Sub-Saharan African countries in the Tropical region are projected as the future hotspots of water scarcity due to rising population pressure and climate variability. Around 87 out of 180 countries will turn into ‘water-stressed’ and 45 countries into ‘absolute water scarcity’ by 2050. Irrigation water demand accounts for 70% of all freshwater withdrawals globally. Due to varying climatic, topographical, and governance conditions, the agriculture techniques in the 54 tropical countries are indigenous to the local conditions. The main objective is to review the challenges in irrigation water management in seven water-stressed Tropical countries among the 54 countries. These countries are identified based on the baseline country data mined from FAO’s AQUASTAT database. A systematic literature review focusing on sustainable irrigation practices, the economic effects of water-pricing tools, and the role of policies and institutions were studied. The discussion centered on environmental sustainability, financial sustainability, institutional sustainability, and the resilience of agriculture to climate variability impacts. Community-based interventions, successful financial models, and policy and institutional reforms were perceived from successful irrigation systems. Implementation of climate-smart agricultural practices, shifting to water-saving technologies and irrigation methods, empowering the institutions, and enforcing policies and regulations to restrict resource overuse are recommended solutions for Sustainable Water Governance.